نشأة وتطور واختصاص القضاء الإداري التايلاندي والمصري : دراسة مقارنة - هاما زكريا (Al-HIKMAH Journal, 2021)
The study aims to shed light on the origin, development and jurisdiction of the Thai and Egypian adminitrative judiciary, as a comparative study, by extrapolating analyzing and comparing the origin, development and jurisdiction of the Thai and Egypian adminitrative judiciary. The study began by listing the origin, development and jurisdiction of the adminitrative judiciary in Thailand and Egypt, follewed by the specialization of the adminitrative judiciary in Thailand and Egypt, then concluded by comparing the origin, development and jurisdiction of the Thai and Egypian adminitrative judiciary, following the method of induction, analysis and comrison. The study found that Thailand and Egypt adopted the unified judicial system at the beginning of its inception and the switched to the dual justice system and the origin of the Thai and Egypian adminitrative judiciary in its old form dates back to the end of the nineteenth century AD, when the Thai Advisory Council was established in 1874 AD, and the Egyptian State Council was established in 1879 AD. The Egyptian efforts succeeded in 1946 AD with the issuance of Law No.112 of 1946 AD establishing the State Council and it has an advisory and judicial function, while Thai efforts succeeded in substantiating the articles of the administrative judiciary in the Thai Constitution of 1974 AD and the Thai Constitution of 1991 amende No.5 of 1995 AD and Thai Constitution of 1997 AD followed the law on establishment of Administrative Court and Administrative Court Procedure 1999 AD, which is the administrative judiciary in its modern form. The Egyptian State Concil incorporated the establishment of the Administrative Court of Justice in 1946 AD, then established the Adminstrative Court in 1949 AD, then completed the establishment of the Supreme Administrative Court in 1995 AD at the top of Judicial section Courts in the State Council, while the Superme Administrative Court and The Administrative Court of First Instance were established in 2001 AD at once. The Thai and Egyptian legislator agree to determine the jurisdiction of the administrative judiciary according to general standard and exclusivele. The jurisdiction of the Thai administrative judiciary is divided between the Superme Administrative Court and The Administrative Court of First Instance, while the jurisdiction of the Egyptian Administrative judiciary is divided between the Superme Administrative Court, the Adminitrative Court of justice, the Disciplinary Courts. The Study proposes to reduce the burden of the Thai supreme administrative court by establishing the administrative court of a degree between the Superme Administrative Court and The Administrative Court of First Instance, which is the administrative court of appeal, in order to reinforce the principle of administrative litigation for more than two degrees, to ensure the conduct of litigation procedures from arbitrary management, which enchances justice for the opponent and give him opportunity to present his grievavce before a court the highest degree, especially with the increase in cases and lawsuits brought to it and accumulated from year to year, which leads to delays in adjudicating cases and achieving justice.